The Effect of Transcranial Direct Current Stimulation on Jaw Motor Function Is Task Dependent: Speech, Syllable Repetition and Chewing - Simione, Meg; Fregni, Felipe; Green, Jordan R. (Frontiers in Human Neuroscience, 2018)
Motor cortex transcranial direct current stimulation (tDCS) has been shown to enhance motor learning in healthy adults as well as various neurological conditions. However, there has been limited data on whether tDCS enhances jaw motor performance during different oral behaviors such as speech, maximum syllable repetition, and chewing. Because the effects of anodal and cathodal stimulation are known to be dependent on task demands, we hypothesized that tDCS would have a distinct effect on the jaw motor performance during these disparate oral behaviors. Ten healthy adults completed speech, maximum syllable repetition, and chewing tasks as their jaw movements were recorded using 3D optical motion capture during sham, anodal, and cathodal tDCS. Our findings showed that compared to the sham condition, jaw displacements during speech and syllable repetition were smaller during anodal stimulation, but larger during cathodal stimulation for syllable repetition and chewing indicating improved performance during anodal tDCS. On the other hand, there were no effects of anodal tDCS during chewing. These results confirm our hypotheses that (1) tDCS induces a significant effect on jaw motor function; (2) its effects are polarity dependent; and (3) its effects are dependent on the task demands on jaw motor function. These findings support future studies exploring the effects of tDCS on persons with oral sensorimotor impairments and the development of therapeutic protocols.